158k views
1 vote
Solve the system with elimination.
x - 2y = 4
3x + y = 6
(²), __)
Enter

User Tim Norman
by
7.3k points

1 Answer

1 vote

Answer:

To solve the system of equations with elimination, we need to eliminate one of the variables by adding or subtracting the equations. In this case, we can eliminate y by multiplying the first equation by -1 and then adding it to the second equation. This gives us:

-1(x - 2y) = -1(4)

3x + y = 6

2x - 5y = 2

Now we can solve for x by dividing both sides by 2:

x - 5y/2 = 1

x = 1 + 5y/2

To find the value of y, we can substitute this expression for x into either of the original equations. Let's use the first one:

x - 2y = 4

(1 + 5y/2) - 2y = 4

Simplifying and rearranging, we get:

-4y + 5y = 8 - 2

y = 6

Now we can plug this value of y into the expression for x and get:

x = 1 + 5(6)/2

x = 16

Therefore, the solution of the system is (16, 6). We can check this by plugging these values into both equations and verifying that they are true.

User Leanne
by
7.4k points